Altered Expression of Par3, aPKC-λ, and Lgl1 in Hippocampus in Kainic Acid-Induced Status Epilepticus Rat Model - Zhang, Chen; Tian, Fafa; Tan, Zheren; Du, Juan; Long, Xiaoyan (Frontiers in Neurology, 2021)
Introduction: Mossy fiber sprouting (MFS) is a frequent histopathological finding in temporal lobe epilepsy (TLE) and is involved in the pathology of TLE. However, molecular signals underlying MFS remain unclear. Partitioning defective 3(Par3), atypical protein kinase C-λ(aPKC-λ), and lethal giant larvae 1(Lgl1) were involved in the neuronal polarity and axon growth. The potential roles of those proteins in MFS and epileptogenesis of TLE were investigated. Material and Methods: The epileptic rat models were established by intracerebroventricular injection of kainic acid (KA). The degree of MFS was measured by using Timm staining, Neuronal loss and the expression aPKC-λ, Par3, and Lgl1 in hippocampus were measured by using immunohistochemistry and western blot analysis. Results: The neuronal loss in CA3 region was observed from 3 days to 8 weeks, while the neuronal loss in the hilar region was observed from 1 to 8 weeks in experimental group. The Timm score in the CA3 region in experimental group was significantly higher than that in the control group from 2 to 8 weeks. Compared with control group, the expressions of Par3 and Lgl1 were upregulated and the expression of aPKC-λ was downregulated in the experimental groups. Positive correlation between the Par3 expression and Timm scores, and the negative correlation between the aPKC-λ expression and Timm scores in CA3 region were discovered in experimental group. Conclusion: The findings of the present study indicated that aPKC-λ, Par3, and Lgl1 may be involved in MFS and in the epileptogenesis of temporal lobe epilepsy.